Retinal Thickness and Microvascular Pattern in Early Parkinson's Disease - Rascunà, Cristina; Russo, Andrea; Terravecchia, Claudio; Castellino, Niccolò; Avitabile, Teresio; Bonfiglio, Vincenza; Fallico, Matteo; Chisari, Clara Grazia; Cicero, Calogero Edoardo; Grillo, Marco; Longo, Antonio; Luca, Antonina; et al. (Frontiers in Neurology, 2020)
A thinning of intraretinal layers has been previously described in Parkinson's disease (PD) patients compared to healthy controls (HCs). Few studies evaluated the possible correlation between retinal thickness and retinal microvascularization. Thus, here we assessed the thickness of retinal layers and microvascular pattern in early PD patients and HCs, using, respectively, spectral-domain optical coherence tomography (SD-OCT) and SD-OCT-angiography (SD-OCT-A), and more interestingly, we evaluated a possible correlation between retinal thickness and microvascular pattern. Patients fulfilling criteria for clinically established/clinically probable PD and HCs were enrolled. Exclusion criteria were any ocular, retinal, and systemic disease impairing the visual system. Retinal vascularization was analyzed using SD-OCT-A, and retinal layer thickness was assessed using SD-OCT. Forty-one eyes from 21 PD patients and 33 eyes from 17 HCs were evaluated. Peripapillary retinal nerve fiber layer (RNFL) and macular RNFL, ganglionic cell layer (GCL), inner plexiform layer (IPL), and inner nuclear layer (INL), resulted to be thinner in PD compared to HCs. Among PD patients, a positive correlation between RNFL, GCL, and IPL thickness and microvascular density was found in the foveal region, also adjusting by age, sex, and, especially, hypertension. Such findings were already present in the early stage of disease and were irrespective of dopaminergic treatment. Thus, the retina might be considered a biomarker of PD and could be a useful instrument for onset and disease progression.